2020
DOI: 10.1177/0886260520916277
|View full text |Cite
|
Sign up to set email alerts
|

The Chivalrous Bystander: The Role of Gender-Based Beliefs and Empathy on Bystander Behavior and Perceived Barriers to Intervention

Abstract: Despite substantial evidence demonstrating a relation between gender-based beliefs and violence against women, there has been little research examining whether sexist attitudes are related to prosocial bystander behavior. Understanding psychosocial influences on bystanders’ behavior could inform bystander training programs on college campuses, and so the current study examined the unique and joint effects of three gender-based attitudes (rape myth acceptance, hostile sexism, and benevolent sexism) and empathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Collective identity has been found to foster empathetic altruism, as women’s understanding of themselves as a social group makes them feel that ‘violence against one woman constitutes automatically also a threat against… others’ ( Kreft, 2019 ). Researchers studying sexual assault in the US have evidenced the role of empathy in promoting bystander action ( Beeble et al, 2008 ; Yule et al, 2020 ). Finally, reciprocal altruism has been observed in contexts where women already had reciprocal economic ties, such as microcredit groups in which women mobilised to support other group members against domestic violence ( Sanyal, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Collective identity has been found to foster empathetic altruism, as women’s understanding of themselves as a social group makes them feel that ‘violence against one woman constitutes automatically also a threat against… others’ ( Kreft, 2019 ). Researchers studying sexual assault in the US have evidenced the role of empathy in promoting bystander action ( Beeble et al, 2008 ; Yule et al, 2020 ). Finally, reciprocal altruism has been observed in contexts where women already had reciprocal economic ties, such as microcredit groups in which women mobilised to support other group members against domestic violence ( Sanyal, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…People often help if they are certain that a situation involves abuse ( Bennett et al, 2014 ; Pugh et al, 2016 ), and may fail to look for more subtle cues indicating that a person is at risk. Individuals with lower levels of self-efficacy ( Yule & Grych, 2020 ), and higher levels of benevolent sexism and rape myth acceptance ( Yule et al, 2020 ) are more likely to perceive situations as low risk.…”
mentioning
confidence: 99%
“…Indeed, in a large sample of US university students, a large proportion of those who did not intervene reported the reason as the incident being “none of their business” ( Hoxmeier et al, 2020 ). The lack of personal responsibility could be influenced by a number of factors, such as moral perceptions of the victim (e.g., promiscuity and intoxication), diffusion of responsibility, or individual characteristics of the bystander ( Bennett et al, 2014 ; Pugh et al, 2016 ; Robinson et al, 2020 ; Yule et al, 2020 ). For instance, lack of pro-social attitudes, low perceived control ( Bennett et al, 2014 ), benevolent sexism, and rape myth acceptance ( Yule et al, 2020 ) have all been related to absence of personal responsibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying subtheme of both forms of sexism, however, is the same: dominance by men (Glick et al, 2004). While previous researchers found that sexism positively related to rape myth acceptance (e.g., Canto et al, 2014;Rollero & Tartaglia, 2018), lower intentions to intervene (e.g., Gracia et al, 2018;Katz et al, 2018), and less intervention after an assault (benevolent sexism only; Yule et al, 2020), little is known about how sexism relates to the recognition of sexually harassing behaviors. Based on the attitudes representing benevolent and hostile sexism, we anticipate that those who perceive women as good, caring creatures who need protection (higher levels of benevolent sexism) will be more likely to identify sexually harassing behaviors.…”
Section: Sexismmentioning
confidence: 97%